Asthma exacerbations · 1: Epidemiology - Johnston, N W (BMJ Group, 2006)
Asthma exacerbations may be triggered by a number of atmospheric and domiciliary environmental factors as well as by those encountered in schools and workplaces. The majority of exacerbations, particularly in children, coincide with respiratory viral infections, most commonly rhinovirus. As most respiratory viruses and many aeroallergens appear in seasonal patterns, asthma exacerbations, particularly those requiring emergency treatment, show analogous seasonal cycles which differ in form in children and adults. While similar in form between the sexes, they differ in amplitude, with boys having higher risks of exacerbation in childhood and women in adult life. Simultaneous exposure of asthmatics with respiratory viral infections to allergens or air pollutants may significantly increase the risks of exacerbation. Access to and compliance with inhaled corticosteroid treatment is an important predictor of the likelihood of asthma exacerbations occurring, including those that occur during respiratory viral infections. Epidemiologically, the degree of asthma control achieved by asthmatics is an important predictor of the likelihood of disease exacerbation including respiratory failure, death, and health service consumption.